Lifestyle habit change related to presenteeism change among Japanese employees - Momoko Tsuchida; Takafumi Monma; Sakiko Ozawa; Ayako Kikuchi; Fumi Takeda (AIMS Press, 2024)
This study aimed to examine the relationship between changes in lifestyle habits and presenteeism change according to sex. This retrospective cohort study was conducted using data from health checkups, the World Health Organization Health and Work Performance Questionnaire (WHO-HPQ) short form, and health insurance claims for 9366 Japanese corporate employees in 2015 and 2016. Changes in 11 lifestyle habits of sleeping, eating, exercise, drinking, and smoking were classified into four patterns by combining lifestyle habits (good/poor): (a) no worsening, (b) worsening, (c) no improvement, and (d) improvement. A multiple regression analysis was conducted for each sex, with changes in the WHO-HPQ score as the objective variable, lifestyle habits change (worsening or improvement) as the explanatory variables, and age, job position, department, diseases, lifestyle habits, and WHO-HPQ score at baseline as adjustment variables. The results showed worsening of good lifestyle habits, such as sleeping, regular exercise, and frequency of drinking in men, while sleeping in women was associated with negative changes in the WHO-HPQ score. On the other hand, the improvement of poor lifestyle habit of sleeping was associated with positive changes in the WHO-HPQ score. These findings suggest that maintaining good lifestyle habits of sleeping for both sexes, and exercising and drinking for men, may be beneficial in maintaining work performance, while improving the poor lifestyle habit of sleeping for women may be beneficial in improving work performance.